2022
DOI: 10.5751/es-13512-270341
|View full text |Cite
|
Sign up to set email alerts
|

Can the center hold? Boundary actors and marginality in a community-based natural resource management network

Abstract: Community-based natural resource management (CBNRM) seeks to align the interests of local communities and conservation institutions. A significant challenge to this realignment is that CBNRM is often implemented in locations with colonial histories of oppression, persecution, and dispossession that have left legacies of inequity and marginalization. Social networks are one method for discerning how marginalized CBNRM actors can negotiate entitlements and agency. Through the lens of social networks, marginaliza… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 66 publications
0
6
0
Order By: Relevance
“…Having contributed to communication strategies and analysed the digital content of CBNRMorganizations in Namibia, including social media, websites, and online forums, the authors identified that digital literacy was an urgent need. Moreover, content analysis from previous research (Al-Shawaf, and Buss, 2021;Castillo-Huitrón et al, 2020;Snorek and Bolger, 2022) has identified misinformation, common misconceptions, and patterns of communication that contribute to misunderstandings. The combination of these methods will provide a comprehensive understanding of the misunderstandings surrounding the sustainable use approach in Western settings and the role of digital literacy in addressing them.…”
Section: Methodsmentioning
confidence: 99%
“…Having contributed to communication strategies and analysed the digital content of CBNRMorganizations in Namibia, including social media, websites, and online forums, the authors identified that digital literacy was an urgent need. Moreover, content analysis from previous research (Al-Shawaf, and Buss, 2021;Castillo-Huitrón et al, 2020;Snorek and Bolger, 2022) has identified misinformation, common misconceptions, and patterns of communication that contribute to misunderstandings. The combination of these methods will provide a comprehensive understanding of the misunderstandings surrounding the sustainable use approach in Western settings and the role of digital literacy in addressing them.…”
Section: Methodsmentioning
confidence: 99%
“…Additional tensions may arise between processes of commodification and market access by investors in communal lands and cultural heritage practices normally considered the remit of Traditional Authorities, given that priming land and resources for external access and investment may impinge on Indigenous access and use (Sullivan and Ganuses 2021). In other words, circumstances in Namibian CBNRM tend rather toward the opposite of the conceptual frame acting as the explanatory anchor for the network analysis presented by Snorek and Bolger (2022), even if elite capture of resource access and use by the Topnaar TA may be of concern to the wider !Khuiseb community.…”
Section: Framingmentioning
confidence: 99%
“…On these issues of (mis)representation I make one final observation regarding the paper's presentation of anthropologist Winifred Hoernlé's work in the early 20th century with peoples associated with the !Khuiseb. Snorek and Bolger (2022:2) write that "[p]rejudicial accounts have also stemmed from anthropologists, including being labeled 'probably the most miserable of all the remnants of the Nama'" (Hoernlé 1985(Hoernlé [1925). To understand this statement made almost 100 years ago by Hoernlé, however, it is necessary to consider the fuller statement within which it is embedded, and to note its positioning within some of the most detailed and respectful research amongst various Nama groupings (Carstens 1985, Bank 2016.…”
Section: Representing Early Ethnographymentioning
confidence: 99%
See 1 more Smart Citation
“…Boundary actors serve as a bridge between disparate actors across a watershed. They provide social learning opportunities across social boundaries (Friedman and Podolny 1992, Perrault 2003, Olsson et al 2004, Pahl-Wostl 2009, Long et al 2013) and support the navigation of intercultural or cognitive barriers between heterogeneous groups (Burt 1992, Cohen and Davidson 2011, Long et al 2013, Snorek and Bolger 2022. By bridging central organizations to other actors across networks, a relational hub can enable the continuity of watershed governance (Cockburn et al 2019b).…”
Section: Introductionmentioning
confidence: 99%